Release of Formic Acid from Copper Formate: Hydride, Proton‐Coupled Electron and Hydrogen Atom Transfer All Play their Role - Pascher, Tobias F. (Chemphyschem, 2019)
Although the mechanism for the transformation of carbon dioxide to formate with copper hydride is well understood, it is not clear how formic acid is ultimately released. Herein, we show how formic acid is formed in the decomposition of the copper formate clusters Cu(II)(HCOO)(3) (−) and Cu(II)(2)(HCOO)(5) (−). Infrared irradiation resonant with the antisymmetric C−O stretching mode activates the cluster, resulting in the release of formic acid and carbon dioxide. For the binary cluster, electronic structure calculations indicate that CO(2) is eliminated first, through hydride transfer from formate to copper. Formic acid is released via proton‐coupled electron transfer (PCET) to a second formate ligand, evidenced by close to zero partial charge and spin density at the hydrogen atom in the transition state. Concomitantly, the two copper centers are reduced from Cu(II) to Cu(I). Depending on the detailed situation, either PCET or hydrogen atom transfer (HAT) takes place.